Evaluation of cardioprotective effect of aqueous extract of Allium cepa Linn. bulb on isoprenaline-induced myocardial injury in Wistar albino rats - Geeta B Kharadi; Kaksha J Patel; Bhargav M Purohit; Seema N Baxi; C B Tripathi (Research in Pharmaceutical Sciences, 2016)
To investigate the cardioprotective potential of the aqueous extract of Allium cepa Linn. bulb in isoprenaline-induced myocardial injury in Wistar albino rats. In vitro total phenolic, total flavonoid content and 2, 2′-diphenyl-1-picrylhydrazyl hydrate radical scavenging activity was measured. Isoprenaline-induced myocardial injury model was used to evaluate in vivo effect of aqueous extract of A. cepa in Wistar albino rats. Seventy two rats were randomly divided in 6 groups. Rats were treated with A. cepa 400 mg/kg and 800 mg/kg doses for 30 days and myocardial injury was produced by subcutaneous injection of isoprenaline (ISO) 85 mg/kg on day 28 and 29. Carvedilol 1 mg/kg for 30 days served as active control. Electrocardiogram parameters, cardiac injury markers, oxidative stress markers and histopathological changes were evaluated in each group and compared using appropriate statistical tests. In vitro evaluation of aqueous extract of A. cepa showed significant antioxidant property. ISO produced significant myocardial injury as compared to normal control group (P < 0.05). Administration of A. cepa in the dose of 400 mg/kg significantly recovered the altered parameters (Troponin-I, Creatine kinase-MB, glutamate-pyruvate transaminase, HR, R-R interval, and oxidative stress markers) compared to disease control group (P < 0.05) while A. cepa in the dose 800 mg/kg recovered the altered parameters (HR, heart weight/body weight ratio, and superoxide dismutase level) compared to disease control group. Histopathological parameters did not recover in the doses of 400 and 800 mg/kg (P > 0.05). The aqueous extract of A. cepa 400 mg/kg was found to be cardioprotective against myocardial injury while A. cepa 800 mg/kg did not show significant cardioprotective activity. So, we presume that A. cepa might be effective within certain dose range only.